A new look at atonement in Leviticus : the meaning and purpose of kipper revisited - Greenberg, James, 1960- (Bulletin for biblical research supplements, 2019)
"A new study of Old Testament atonement in the Priestly Literature that employs a modified text-immanent strategy to investigate how sacrifice works. Focuses on Priestly Torah texts found in Leviticus 1-16, Exodus and Numbers"--